DESCRIPTION OF THE GLORY OF 'RAM' IN THE PURANAS - Pandey, Km. Prerna; Ojha, Devendra Nath; Umashankar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The description of 'Ram' ki Mahima' in the Puranas is a very extensive and profound subject. Ram ki Mahima is described mainly in various texts like "Ramayana", "Mahabharata", "Vishnu Purana", "Shiva Purana", and "Bhagavata Purana". Lord Rama, the symbol of Sattvic ideals of Hinduism, is worshiped as an incarnation of Maryada Purushottam and Vishnu. Every aspect of his life, like ideal son, husband, friend, warrior, king, etc., is praised in Ramayana. In this research paper I have highlighted the various dimensions of Rama's glory in the Puranas, presenting aspects of his godliness, virtuous conduct, and his divinity.